Bankruptcy Analysis Of Financial Statements Of Telecommunications Sub Sector Companies Listed On The Indonesia Stock Exchange For The 2016-2019 Period - Arvina arham (Pustaka Digital Indonesia, 2021)
The purpose of this study is to analyze bankruptcy in the financial statements of companies in the telecommunication sub-sector listed on the Indonesia Stock Exchange for the 2016-2019 period using the Altman Z-Score method. The research method used is a quantitative method using secondary data. Sources of data used in this study came from the company's financial statements PT Telekomunikasi Tbk, PT XL Axiata Tbk, and PT Indosat Tbk. Based on the Altman Z-Score method using 5 types of ratios, namely working capital/total assets, retained earnings/total assets, earnings before interest and taxes/total assets, market value of equity/book value of debt, and sales/total assets. With the formula Z-Score = 1.2X1 + 1.4X2 + 3.3X3 + 0.6X4 + 0.1X5. With the assessment criteria Z-Score > 2.99 categorized as a healthy company, 1.81 < Z-Score < 2.99 categorized as a company that is in the gray area so that the possibility of being saved and the possibility of bankruptcy is equally dependent on of the company's management policy decisions as decision makers. Z-Score <1.81 is categorized as an unhealthy or bankrupt company. The results showed that PT Telekomunikasi Indonesia Tbk in 2016-2019 was in a healthy condition. PT XL Axiata Tbk and PT Indosat Tbk in 2016-2019 were in a bankrupt or unhealthy condition.